Spontaneous use of vocabulary learning strategies - Zybert, Jerzy (Adam Mickiewicz University, 2010)
The paper argues that language learners employ learning strategies naturally. To corroborate the claim it presents a research on vocabulary learning strategies and provides a quantitative and qualitative analysis of the findings and concludes with some pedagogical suggestions.